Pengaruh Kualitas Pelayanan, Kepercayaan, Citra Perusahaan Terhadap Kepuasan Nasabah Di BCA EXPRESS Met Mall Cibubur - Zakaria Indra Hasiholan Purba; Ricky Talumantak (Universitas 45 Surabaya, 2023)
The purpose of this study was to determine how the influence of service quality, trust, and company image on customer satisfaction at BCA EXPRESS Met Mall Cibubur. The population of this study consisted of regular visitors to BCA EXPRESS Met Mall Cibubur. The sampling method used is purposive sampling, with a total of 100 respondents. Multiple linear regression analysis was performed using IBM SPSS 25 software. The results showed that service quality and trust has a significant effect on customer satisfaction, but corporate image have no effect. However, service quality, trust, and corporate image all have an influence on customer satisfaction.